International Student Mobility in Israel - Bamberger, Annette (International Higher Education, 2018)
The government of Israel is seeking to double the number of incoming international students. This article outlines the antecedents of this policy and identifies issues that are emerging as the state seeks to broaden the nature and purposes of internationalization. It problematizes the policy and raises questions concerning the development of international student mobility in Israel.